Penggunaan Bahasa di Ruang Publik Kota Samarinda - Zaka, Istifatun (Innovative: Journal Of Social Science Research, 2024)
The use of language cannot be separated from social life. People's use of language can be seen in public and private areas. Language as a national identity can show the existence of a nation. Therefore, the use of language in society is one indicator of the existence of a nation. Samarinda, as a city in Indonesia, is known for the diversity of its people. Therefore, research related to language use in the public spaces of the city of Samarinda can provide an overview of the language situation in this city. This research is a qualitative descriptive study and was conducted on outdoor language signs in public spaces in the city of Samarinda, especially in the area along the banks of the Mahakam River. The results of the research show that the use of language in outdoor language signs in public spaces in the city of Samarinda can be divided into 3 groups, namely: 1) Indonesian language; 2) foreign language; and 3) language combination. Language combinations include the use of Indonesian and regional languages, as well as regional languages and foreign languages. Keyword: the use of language, public space, Samarinda City